Analysis of Particle Pollutant Dispersion and Flow Field in a Naturally Cross-Ventilated Model Building - Amir Hakamian (مهندسی و مدیریت ساخت)
This study, firstly, gives a summary about natural ventilation and particle dispersion, and, then, presents the research reported so far in these areas. As well as these, the research methodology, the sub-grid scale model equations used in the simulation, namely, Wall-Adapting Local Eddy-viscosity (WALE), Standard Smagorinsky-Lilly Model (SSLM) and Dynamic Smagorinsky-Lilly Model (DSLM), computational domain and other requisite conditions for the simulation have been illustrated. In order to ensure of the validity of the present results, direct comparisons with available experimental results have been made. These results show that the sub-grid scale WALE model is more accurate than the other models in the simulation of the particle dispersion in a model building with natural ventilation, and SSLM sub-grid scale model estimates the least particle concentration in the building. In addition, these results illustrate that the convective flux and turbulent diffusion flux have the key role in the pollutant transportation process around the entrance of model building. Also, the influence of convective flux is more than that of diffusion flux as one moves along the length of the model building.